2008
DOI: 10.1089/dna.2007.0702
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of HER2 Genotypes as Molecular Markers on Breast Cancer Outcome

Abstract: Alterations of the human epidermal growth factor receptor 2 (HER2) protooncogene have been implicated in the carcinogenesis and prognosis of breast cancer. A polymorphism has been identified at codon 655 (ATC/isoleucine to GTC/valine [I655V]) in the transmembrane domain-coding region of this gene, which may be associated with the risk of breast cancer. In this study we aimed to determine whether the risk of breast cancer is associated with the I655V polymorphism of HER2 transmembrane domain-coding region at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The results of many subsequent case-control studies [15,18,24,26,27,29,31] supported the association. Two studies by Millikan et al [15] and Mutluhan et al [30] showed no overall association between HER2 Ile655Val polymorphism and breast cancer, but an positive association was observed in women under 45 with a family history of breast cancer and in women older than 60, respectively. The more interesting finding revealed by Cox et al [22] showed an inverse association which indicated that the polymorphism may be associated with a modest decrease, rather than an increase in risk of breast cancer.…”
Section: Publication Biasmentioning
confidence: 95%
“…The results of many subsequent case-control studies [15,18,24,26,27,29,31] supported the association. Two studies by Millikan et al [15] and Mutluhan et al [30] showed no overall association between HER2 Ile655Val polymorphism and breast cancer, but an positive association was observed in women under 45 with a family history of breast cancer and in women older than 60, respectively. The more interesting finding revealed by Cox et al [22] showed an inverse association which indicated that the polymorphism may be associated with a modest decrease, rather than an increase in risk of breast cancer.…”
Section: Publication Biasmentioning
confidence: 95%
“…Twenty‐six studies with a total number of 15,940 case and 19,148 controls were included in this analysis . Among these studies, 26 and 3 studies were considered for meta‐analysis concerning ERBB2 Ile655Val and Ala1170Pro polymorphisms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, four sizeable eligible studies [2][3][4][5] (1,745 cases and 1,921 controls) have not been included in this meta-analysis, even though they satisfied the search criteria. Specifically, the study by Millikan et al [2] has provided separate data on African (754 cases and 676 controls) and Caucasian (1,261 cases and 1,132 controls) subpopulations.…”
Section: To the Editormentioning
confidence: 99%
“…Under the light of the above, we put all studies into a new meta-analysis, including the four sizeable eligible studies [2][3][4][5], and we observed that the HER2 codon 655 polymorphism was significantly correlated with breast cancer risk in the Val versus Ile allele contrast model (OR 1.10, 95% CI 1.02-1.19, random effects model) and the dominant model (OR 1.10, 95% CI 1.01-1.19, random effects model). However, we did not find any associations in additive genetic model (the homozygote codominant: OR 1.15, 95% CI 0.93-1.43; the heterozygote codominant: OR 1.07, 95% CI 0.99-1.16; the recessive model: OR 1.11, 95% CI 0.90-1.35, random effects model).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation